A circular Eddy current probe using miniature fluxgates for multi-orientation slit evaluation in steel components - Mohd Mawardi, Saari; Nurul A'in, Nadzri; Mohd Aufa Hadi Putera, Zaini; Mohd Herwan, Sulaiman; Kiwa, Toshihiko (Pleiades Publishing, 2023)
Detection of crack propagation, such as its direction and depth, is one of the important aspects in ensuring the safety and reliability of steel structures. This study presents a development of a circular eddy current excitation probe using a planar differential miniature fluxgate to detect vertical and horizontal slits. The probe utilizes a circular eddy current excitation technique that induces multi-direction eddy currents in a mild steel plate and a sensing configuration based on the tangential magnetic response. The performances of the developed probe were characterized based on line and 2D map scans of the magnetic response due to the induced eddy currents in mild-steel samples from different orientations and depths of artificial slits. The results showed that the developed probe obtained a signal correlation with the slit depth at different slit orientations. The vertical and horizontal slits were able to be visualized from the magnetic field distribution, where the differential imaginary component had a better detection sensitivity for the vertical slits represented by the measured peak-to-peak signals. The detection of multi-orientation slits revealed that the slit orientation could be estimated from the magnetic response maps with a detection limit of 5 mm in the slit length and 0.5 mm in the slit width, respectively.